Narratives of War: Acehnese Perception of the Prang Kaphe in 19th/20th Century Colonial Era (Malay Literature, 2013)
The so-called narratives of war refer to hikayat literature composed especially during the Dutch occupation of Aceh in 19th century and early 20th century; they relate mostly battles and exploits of the Acehnese heroes and fighters against the Dutch incursion, beginning in 1873. Since war fought against the Dutch was considered as a jihad war, these hikayats then came to be known as the Hikayat Prang Sabi (or the story of the war in the path of God) or Hikayat Prang Kaphe (or war against the infidels). Besides their cultural and historical significance, these hikayats are also reliable documents to understand the Acehnese perception of the jihad war or the prang kaphe. This essay then is an attempt to study these hikayats as sources in reading the Acehnese perception of jihad. To facilitate analysis, three war hikayats viz. the Hikayat Prang Sabi, Hikayat Prang Cut Ali and Hikayat Prang Rundeng will be chosen as focus of critical study. From the analysis the essay comes to an interesting conclusion: that contrary to popular belief, the jihad war did not have a similar grip on every Acehnese; apparently there were varied responds and emotions towards the war which influence Acehnese perception towards the whole ideology of jihad.Keywords: narrative of war, Hikayat Prang Kaphe, Acehness perception, jihad